Gestión administrativa y financiera y su incidencia en la toma de decisiones del banco d-miro, cantón Quevedo, año 2014. - Piguave Toaza, Diana Mariuxi (2016)
For information on the administrative and financial management and its impact on decision making D-Miro Bank, 2014 Quevedo canton was necessary to use methods and techniques that allowed achieve information according to the subject of research, including methods are the analytical method which analyzes in detail each department's compliance with policies in the administrative management of the branch generally observing the causes, effects and how to influence decision-making and the implications of how it affects the Institution. Primary sources were also used to obtain first-hand information through surveys direct to the people involved formed by taking into account the suggestions, in order to meet the different points of view for it was necessary to achieve population data in this case randomly selected customers. The final results of a comparative analysis of financial statements indicated that the Bank has an economic balance its assets and liabilities increased compared with the previous period, financial indicators showed that the index of profitability, financial efficiency is higher compared with the year not its liquidity above which decreased so is necessary to analyze the policies and procedures for maintaining the organization to become more efficient. Coming to conclusions which show that the institution has accepted the financial services it offers, a so there shortcomings that limit their interfering in meeting existing targets, so you must plan the development of their functions allowing direct activities, organize and control operations performed in terms of its evaluation of the financial statements which the two periods were compared you show the total assets had an economic differentiation of 2013 was $ 63,391.78 while for 2014 increased by $ 84,721.18 with a total share of 33.65%, indicating that the company has assets that can be converted into cash in the short or medium term. Equity also shows an increase of $ 13,605.76 giving a percentage of 13.50%, representing the economic power that the partners to the company indicating that the board has control of the institution.